KONFLIK SUNNI-SYIAH DI SAMPANG DITINJAU DARI TEORI SEGITIGA KONFLIK JOHAN GALTUNG - Zattullah, Nour (JURNAL ILMU BUDAYA, 2021)
Behind Indonesia’s plurality, there is vulnerability to social conflict which can be caused by many differences in Indonesia. One of the social conflicts in Indonesia that has not yet reach a comprehensive resolution is the Sunni-Shia conflict in Sampang, East Java. This article is aimed at providing in-depth analysis on the conflict of Sunni-Shia in Sampang using Johan Galtung's conflict triangle theory. This study used qualitative method in which data were collected through library research and analyzed descriptively. This study revealed that the Sunni-Shia conflict in Sampang was not only caused by differences in religious teaching between Sunni and Shia, but also due to the deep hatred by Sunni followers towards Shia followers, the assumption that Shia teaching can disrupt the social order, and Sunni followers’ unreasonable prejudices toward Shia. This has subsequently escalated into an attitude of rejection of Shia teaching and continued into violence against Shia followers.